Does a higher American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI‐RADS) score forecast an increased risk of malignancy? A correlation study of ACR TI‐RADS with FNA cytology in the evaluation of thyroid nodules. Issue 7 (20th February 2020) - Modi, Lopa; Sun, Wei; Shafizadeh, Negin; Negron, Raquel; Yee‐Chang, Melissa; Zhou, Fang; Simsir, Aylin; Sheth, Sheila; Brandler, Tamar C.
Abstract : Background: Ultrasound has become the initial approach to evaluating thyroid nodules, facilitating the distinction between benign and malignant nodules based on composition, echogenicity, nodule border or margin, shape, the presence of calcifications, and nodule dimensions. The American College of Radiology (ACR) recommended the Thyroid Imaging Reporting and Data System (TI‐RADS) as a classification system to standardize thyroid ultrasound reports and to predict the probability of malignancy in thyroid nodules using a scoring system (TR1‐TR5) based on multiple ultrasound characteristics and nodule size. Fine‐needle aspiration (FNA) is recommended as the next step for nodules that warrant further workup. The authors assessed the accuracy of the ACR TI‐RADS based on the corresponding FNA cytology results (Bethesda system diagnoses I‐VI). Methods: ACR TI‐RADS ultrasound reports and corresponding FNA cytology diagnoses from January 1, 2018 to August 30, 2018 were evaluated. Results: From January 1, 2018 to August 30, 2018, 2306 thyroid ultrasound‐guided FNAs were performed at our institution. Of 2306 cases, 361 had ACR TI‐RADS reports available. The majority of FNAs were TR4 (180; 49.9%) or TR3 (108; 29.9%). No TR2 or TR3 nodules were associated with Bethesda category V or VI diagnoses. The majority of TR4 nodules (142 of 180; 78.9%) and TR5 nodules (42 of 65; 64.6%) exhibited benign (Bethesda category II) cytology. Fourteen TR5 cases (21.5%) had malignant (Bethesda category VI) cytology. Conclusions: Although there were no TR2 or TR3 malignant (Bethesda category VI) diagnoses, and there were only a few malignancies in the TR4 and TR5 categories, the current results reassert the notion that the ACR TI‐RADS scoring system shows at least some correlation between benign or malignant cytology diagnoses, as illustrated by the greater number of malignant cases in the higher ACR TI‐RADS categories. Abstract : Particular ultrasound features from the American College of Radiology's Thyroid Imaging Reporting and Data System (TI‐RADS) scoring system are quantified and correlated with the fine‐needle aspiration diagnosis. Although no cases are positive for malignancy (Bethesda category VI) in the TI‐RADS 2 (TR2) and TR3 categories, and only small percentages are positive in the TR4 and TR5 categories, the current results reassert the notion that this scoring system shows at least some correlation between benign or malignant cytology diagnoses, as illustrated by the increased number of malignant cases in the higher TI‐RADS categories.